ロケット ニヨル セイイオン ソセイ ノ カダイ - 畚野, 信義; フゴノ, ノブヨシ; 水津, 武; スイツ, タケシ; 厳本, 厳; イワモト, イワオ; FUGONO, Nobuyoshi; SUITSU, Takeshi; IWAMOTO, Iwao (国立極地研究所, 1975)
P(論文) 高度80～108 kmにおける正イオン組成の観測によりNO^+と0_2^+のほか,数種の金属イオンがE層領域で,またD層領域ではhydractedイオンが観測された. A positive ion mass spectrometer was flown on the S-210JA-12 rocket at Syowa Station in the Antarctic Region (69°00'S, 39°35'E), at 13:00 LT, on Feb. 11, 1972. Measurements were obtained from about 108 km, its apogee, to about 80km on descent. A few metal ions in E-region and hydracted ions in D-region of the ionosphere were observed in addition to the main NO^+ and O^+_2 profiles. departmental bulletin paper